The Effectiveness of Modern Physics Learning Tools Using the PhET Virtual Media Assisted Inquiry Model in Improving Cognitive Learning Outcomes, Science Process Skills, and Scientific Creativity of Prospective Teacher Students - Susilawati Susilawati; Aris Doyan; Chistine P. Abo; Chester Ian Sotto Pineda; Lalu Muliyadi (Postgraduate, University of Mataram, 2022)
This study aims to test the effectiveness of developing modern physics learning tools using an inquiry model with the help of PhET virtual media in improving cognitive learning outcomes, science process skills, and creativity of prospective teacher students. The development of these learning tools uses a 4D development research model, namely define, design, develop and disseminate. The sample used in this study were all undergraduate students in one class who took modern physics courses with a total of 20 people. The tests given are in the form of cognitive tests, science processing skills tests, and creativity tests. The improvement in learning outcomes was analyzed using the N-gain test. The results of the N-gain analysis for all aspects indicate that the use of these devices has increased, namely cognitive learning outcomes, science process skills, and student creativity with a high category. These results indicate that the use of physics learning tools modern use of the inquiry model with the help of virtual media PhET is effective for cognitive learning outcomes, science process skills, and scientific creativity of prospective teacher students